The importance of functional tests to assess the effect of a new CFTR variant when genotype–phenotype correlation is not possible. Issue 5 (30th March 2017) - Hinzpeter, Alexandre; Reboul, Marie‐Pierre; Callebaut, Isabelle; Zordan, Cécile; Costes, Bruno; Guichoux, Julie; Iron, Albert; Lacombe, Didier; Martin, Natacha; Arveiler, Benoit; Fanen, Pascale; Fergelot, Patricia; et al.
Key Clinical Message: In vitro functional tests aimed to investigate CFTR dysfunction appear critical to help elucidate the functional impact of new variants of uncertain clinical significance and solve inconclusive cases, especially in early deceased newborns. Abstract : In vitro functional tests aimed to investigate CFTR dysfunction appear critical to help elucidate the functional impact of new variants of uncertain clinical significance and solve inconclusive cases, especially in early deceased newborns.